Reassessment of autoreactivity of the broadly neutralizing HIV antibodies 4E10 and 2F5 and retrospective analysis of clinical safety data - Vcelar, Brigitta; Stiegler, Gabriela; Wolf, Hermann M; Muntean, Wolfgang; Leschnik, Bettina; Mehandru, Saurabh; Markowitz, Martin; Armbruster, Christine; Kunert, Renate; Eibl, Martha M; Katinger, Hermann (AIDS (London), 2007)
The broadly neutralizing recombinant human HIV-1 antibodies 4E10, 2F5 and Igh1b12 are reported to have autoreactive potential, which is significant for HIV-1 vaccine development and passive immunotherapy using these antibodies. To investigate the clinical relevance of these findings in subjects receiving passive immunotherapy with these antibodies. Four types of investigations were performed: (1) Investigation of clotting parameters in an ongoing clinical study with 4E10, 2F5 and 2G12. (2) Mixing experiments of pooled plasma with the same antibodies. (3) Retrospective analysis of serum from patients who received passive immunotherapy with 4E10, 2F5 and 2G12 either alone or in combination. (4) Assessment of clinical safety data obtained after 418 infusions with these antibodies. Standard clinical assays confirmed that 4E10 showed low-level cross-reactivity with cardiolipin, while previously reported cardiolipin cross-reactivity for 2F5 could not be confirmed. High serum titers of 4E10 induced mild prolongation of the activated partial thromboplastin time, which resolved with the wash out of 4E10. Neither 2F5 nor 2G12 affected coagulation. Repeated high-dose infusions of the monoclonal antibody combination were well tolerated with no incidence for thrombotic complications after 418 infusions in 39 subjects. Monoclonal antibody 4E10 but not 2F5 or 2G12 showed autoreactive binding specificities. Infusion of 4E10 resulted in transient low anticardiolipin titers. Although an increased thromboembolic risk cannot definitely be excluded, this risk appears to be low and likely depend on underlying disorders.